Domestic revenue mobilization in developing countries : five essays on the contribution of property taxation - (:unkn) unknown (My University, 2024)
Domestic revenue mobilization is currently considered one of the most potent tools for financing development in developing countries. Moreover, it is recognized that domestic revenues can contribute significantly to achieving the 2030 Agenda Sustainable Development Goals (SDGs) and the African Union's 2063 Agenda.. The question then is which national fiscal instruments governments can rely on to finance their economies. From this perspective, many practitioners and researchers have argued that property taxation, long neglected, can play an essential role in increasing domestic revenues.The aim of this thesis is twofold. First, it seeks to revisit the main determinants of property taxation identified in the literature and explore the mechanisms through which these factors can influence the collection of property tax revenues. Second, it provides insight into specific institutional factors affecting property tax collection in Sub-Saharan Africa. On the whole, the thesis assesses how property taxation can contribute to the overall mobilization of tax revenues.The findings of the thesis contribute to a deeper understanding of property taxation policies in developing countries. The thesis is divided into two parts, consisting of six chapters, including an introductory chapter. The first part, comprising Chapters 2, 3, and 4, offers a comprehensive review of the main determinants of property tax revenues. The second part, which includes Chapters 5 and 6, focuses on Sub-Saharan Africa and investigates institutional factors influencing property tax revenue mobilization in these countries.Chapter 2 explores the relationship between property tax revenue, income inequality, and urbanization in 115 developing and developed countries from 2000 to 2018. The results show that urbanization leads to an increase in property tax revenue in both developing and developed countries, though the relationship differs across regions. Urbanization also reduces income inequality,
Keywords: African Research